The Role of Mediation of Customer Satisfaction in Service Quality Relationship on Hospital Patient Loyalty in Indonesia - Siti Fatonah (International Journal of Supply Chain Management, 2019)
Services in the service sector have a strategic role in creating competitive advantage and value for customers. The efforts that need to be done in improving the competitive advantage is through customer satisfaction and loyalty. The study aims to examine the effect of services quality (Servqual) on satisfaction and loyalty of patient as the service users of BPJS hospital services in Central Java. The study also proves the importance of services quality (Servqual) in achieving patient loyalty. The study took a sample of hospital patients in Central Java a total of 184 patients. The sampling technique in this research is by using purposive sampling. The result of research provides empirical evidence that service quality has a significant effect on patient satisfaction. Service quality significantly affects the patient loyalty. Also, patient satisfaction has a significant effect on patient loyalty.